KEY ASPECTS OF INVESTMENT MARKET MANAGEMENT (The Conference Hub, 2026)
The article discusses the main aspects of investment market management. The stages of planning the main directions of the investment market are studied. The decisive influence of idle funds on the investment market is described. The tasks of improving investment market management are based on.